2001
DOI: 10.1128/iai.69.10.6044-6054.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of aBacteroides caccaeTonB-Linked Outer Membrane Protein Identified by an Inflammatory Bowel Disease Marker Antibody

Abstract: Commensal enteric bacteria are a required pathogenic factor in inflammatory bowel disease (IBD), but the identity of the pertinent bacterial species is unresolved. Using an IBD-associated pANCA monoclonal antibody, a 100-kDa protein was recently characterized from an IBD clinical isolate of Bacteroides caccae (p2Lc3). In this study, consensus oligonucleotides were designed from 100-kDa peptides and used to identify a single-copy gene from the p2Lc3 genome. Sequence analysis of the genomic clone revealed a 2,84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Several OTUs correspond to bacterial species associated with inflammatory diseases or insulin resistance, including Bilophila wadsworthia, 16 Bacteroides caccae 17 or Escherichia coli. 18 Moreover, 21 belonged to the Lachnospiraceae family, which is increased in alcoholic patients with high gut permeability 9.…”
Section: Resultsmentioning
confidence: 99%
“…Several OTUs correspond to bacterial species associated with inflammatory diseases or insulin resistance, including Bilophila wadsworthia, 16 Bacteroides caccae 17 or Escherichia coli. 18 Moreover, 21 belonged to the Lachnospiraceae family, which is increased in alcoholic patients with high gut permeability 9.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary studies in mice have also brought evidence of the role of P fluorescens in the pathogenesis of IBD (S.I. 15 Furthermore, several studies have provided evidence of seroreactivity against Saccharomyces cerevisiae in adult and pediatric series. I2-expressing bacteria are localized in mucosal lesions in humans with CD, and the I2-encoded protein is the target of a disease-associated antibody.…”
mentioning
confidence: 76%
“…pANCAs in IBD have been shown to be reactive with determinants of E coli, B caccae, and mycobacteria. 15 In experimental animal models, it has been demonstrated that anaerobic bacteria present in the colonic flora can cause deep colonic lesions and induce a severe inflammatory response when the mucosal barrier is broken. Anti-OmpC antibodies have been detected in 24% of children with CD and 11% of children with UC.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off level for positivity was set at 0.5 for I2 and 0.6 (children) and 1.0 (adults) for OmpW. 39 …”
Section: Methodsmentioning
confidence: 99%